A comparative study of Turkey, Lebanon and Jordan: host country conditions and Syrian refugee women’s reproductive health - Erol, Isil (2020)
This work project explores the differences in the reproductive health of Syrian refugee women in Turkey, Lebanon and Jordan based on three independent factors, which are gender in/equality, pre-existing general women’s health and the official importance given to national health care services. These countries are chosen because Turkey, Lebanon and Jordan are the countries who host the most crowded Syrian refugee populations. This research investigates whether or not these factors have an impact on the Syrian refugee women’s reproductive health in these three host countries. The research includes a quantitative analysis with the help of SPSS statistical program and a general and country-based literature reviews. My data comes from the World Values Survey and the CIA World Factbook. It is important to raise these questions in this field because the refugee influx is one of the most important issues in the world in the last decade, and refugee women are one of the most vulnerable populations whose health status has been affected by.